KEDUDUKAN PEREMPUAN DALAM DOMESTIK DAN PUBLIK PERSPEKTIF JENDER (Suatu Analisis Berdasarkan Normatifisme Islam) - Intan, Salmah (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2014)
This article aims to analyze whether the position of women in the domestic sphere and the public from a gender perspective, according to Islamic normativism. Gender equality can be understood as a concept that refers to the roles and responsibilities of men and women as a result of social construction that can be changed in accordance with the changing times. Basically Islam does not regulate the area of women and men in the schematic. Islam leaving certain areas to be regulated by human reason based on the demands that are constantly evolving. This view is believed should not deviate from the spirit and teachings of the religion itself, because basically we all recognize the universality of religion from the outset. Without prudence, universality and ease of religion will be lost to the ages.